133k views
2 votes
Solve the system with elimination.
x - 2y = 4
3x + y = 6
? ]

Solve the system with elimination. x - 2y = 4 3x + y = 6 ? ]-example-1
User Bronwyn
by
4.8k points

2 Answers

6 votes
x = 16/7, y = -6/7

For elimination I will multiply the first equation by -3 to get the x to cancel

x - 2y = 4 --> -3x + 6y = -12

Now we bring back the other equation and treat it like an addition problem:

-3x + 6y = -12
3x + y = 6
+———————
7y = -6

y = -6/7

To get x we will use this y-value and plug it into one of the equations:

3x + y = 6,
3x + (-6/7) = 6
3x - 6/7 = 6
3x = 48/7
x = 16/7

So the solution is x = 16/7, y = -6/7, and if you are ever unsure you can put both of these values into both system of equations to see if the equations are true.
User Faziki
by
4.7k points
5 votes

\bold{FULL ANSWER:}
Solve the system with elimination. x - 2y = 4 3x + y = 6 ? ]-example-1
User Parselmouth
by
4.4k points